2017
DOI: 10.1371/journal.pone.0173475
|View full text |Cite
|
Sign up to set email alerts
|

Flavour-enhanced cortisol release during gum chewing

Abstract: There is some evidence to suggest that chewing gum reduces chronic stress. However, it remains controversial how the taste and odour properties of chewing gum influence stress. The present study was designed to investigate this issue in human subjects. Using an enzyme-linked immunosorbent assay, we tested salivary cortisol concentration, which is thought to be a stress marker, in 96 adults who chewed gum with different combinations of taste and odour. Subjects could discriminate between the types of gum withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Chewing was thought to affect stress modification in humans; two studies suggested that the neural mechanism by which chewing gum reduces stress involves the prefrontal cortex, which then affects the hypothalamic-pituitary-adrenal axis and autonomic nervous system activity [ 6 ]. Besides, chewing was tightly linked to hedonic (emotional) systems in the brain [ 7 ]. Chewing gum was not identified as anxiety and stress management intervention in guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Chewing was thought to affect stress modification in humans; two studies suggested that the neural mechanism by which chewing gum reduces stress involves the prefrontal cortex, which then affects the hypothalamic-pituitary-adrenal axis and autonomic nervous system activity [ 6 ]. Besides, chewing was tightly linked to hedonic (emotional) systems in the brain [ 7 ]. Chewing gum was not identified as anxiety and stress management intervention in guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, various physiological reactions evoked by taste stimuli depending on the quality and/or hedonic tone have been more or less used for the objective evaluation of food and beverage hedonics (e.g., positive vs. negative; palatable vs. aversive; pleasant vs. unpleasant; acceptable vs. rejective). For example, taste effects can be observed in autonomic nerve activity such as salivary secretion [5,6], heart rate [7,8], and facial blood flow [9,10], hormonal changes such as insulin [11] and cortisol secretion [12], motor reactions such as facial expressions [13][14][15][16][17] and bodily reactivity [17], and brain activity [18][19][20][21]. A recent study from our lab revealed that pleasant and unpleasant edibles tended to elicit decreased and increased oxyhemoglobin (oxyHb) levels, respectively, within the ventral part of the anterior prefrontal cortex, suggesting that monitoring of oxyHb in this region may prove useful for the objective evaluation of food and beverage hedonics [21].…”
Section: Introductionmentioning
confidence: 99%
“…These findings may not necessarily be fully transferable to humans, since all of these studies were conducted in animals (11). In a human study, Hasegawa et al (21) showed the gum mastication increased the saliva secretion. In the present study, we investigated the effect of substance hardness on the saltiness threshold, then showed that chewing hard Gumi reduced the saltiness threshold.…”
Section: Discussionmentioning
confidence: 99%